2017
DOI: 10.3390/nu9020122
|View full text |Cite
|
Sign up to set email alerts
|

An Exercise‐Only Intervention in Obese Fathers Restores Glucose and Insulin Regulation in Conjunction with the Rescue of Pancreatic Islet Cell Morphology and MicroRNA Expression in Male Offspring

Abstract: Paternal obesity programs metabolic syndrome in offspring. Low-impact exercise in obese males improves the metabolic health of female offspring, however whether this occurred in male offspring remained unknown. C57BL/6NHsd (Harlan) mice were fed a control diet (CD; 6% fat, n = 7) or a high-fat diet (HFD; 21% fat, n = 16) for 18 weeks. After 9 weeks, HFD-fed mice either remained sedentary (HH, n = 8) or undertook low-moderate exercise (HE, n = 8) for another 9 weeks. Male offspring were assessed for glucose/ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 45 publications
0
45
0
Order By: Relevance
“…We chose this approach to avoid stress associated with forced exercise protocols in the dams. Recent studies have reported that paternal exercise (>3 weeks) can mitigate the detrimental effects of paternal obesity on offspring glucose tolerance, adiposity, and pancreatic β-cell mass; vascular function was not assessed (McPherson, Lane, Sandeman, Owens, & Fullston, 2017;McPherson, Owens, Fullston, & Lane, 2015;Stanford et al, 2018). In our study, the mating pairs were set up nightly and males were removed immediately after breeding was confirmed (visible by a vaginal plug).…”
Section: Discussionmentioning
confidence: 98%
“…We chose this approach to avoid stress associated with forced exercise protocols in the dams. Recent studies have reported that paternal exercise (>3 weeks) can mitigate the detrimental effects of paternal obesity on offspring glucose tolerance, adiposity, and pancreatic β-cell mass; vascular function was not assessed (McPherson, Lane, Sandeman, Owens, & Fullston, 2017;McPherson, Owens, Fullston, & Lane, 2015;Stanford et al, 2018). In our study, the mating pairs were set up nightly and males were removed immediately after breeding was confirmed (visible by a vaginal plug).…”
Section: Discussionmentioning
confidence: 98%
“…We have complete lifespans and detailed information on the socioeconomic and family structure for 4,593 children of 1,407 former POWs and 15,310 children of 4,960 non-POW veterans. We are not aware of other large-sample studies in human populations that examine the reversibility of epigenetic transmission as seen in animal studies with maternal dietary supplementation ( 28 , 29 ), maternal licking of offspring ( 30 ), and exercise of mature males in the case of metabolic health ( 31 ). Data limitations preclude the study of the long-term impact of ex-POW status on children’s older age mortality in more recent populations even though the effect of harsh conditions during wartime captivity on the mortality, health, and personality of World War II POW camp survivors has been documented ( 32 35 ).…”
mentioning
confidence: 99%
“…Thus, this novel finding, in the absence of any weight loss difference, uncovers a whole plethora of potential research that can be undertaken in our paternal stress model. Transgenerational modifications to offspring metabolism is well-evident, primarily based on studies of paternal diets and their impact on offspring metabolic and endocrine function [ 67–69 ] but this has not been extensively explored in the context of paternal stress. Only a few transgenerational paternal stress models have explored metabolic changes in the offspring.…”
Section: Discussionmentioning
confidence: 99%